Inclusivity and sustainable development - Tandon, B.B.; Garg, Arunesh (2009)
The world community has recognised the relationship of social and economic growth with environment in the recent times. The concept of sustainable development seeks to draw attention of mankind to this relationship. Sustainable development implies development that meets the needs of the present without compromising the ability of future generations to meet their own needs. Tremendous economic progress has been seen by the mankind in recent times, but this has come at the cost of deterioration of natural resources. Further, only a small section of the society has cornered the fruits of economic development. This entails that sustainable development is required to be revisited in terms of inclusiveness. The government and bureaucrats will have to work towards making the growth more participatory and inclusive so as to ensure sustainable development. There has to be a change in the mind set of politicians and bureaucrats to ensure that governance is viewed and shaped to extend to the grassroots to influence well-being of all sections of the society. - Reproduced.
Keywords: Sustainable development